The combat edge - United States. Air Force. Air Combat Command (Langley Air Force Base, VA : U.S. Air Force, Air Combat Command, 1992)
Air Combat Command's (ACC's) mishap prevention magazine, written by and for ACC people, is dedicated to providing command personnel with flight, weapons and ground safety information.
Jan. 1998; title from title screen (viewed July 29, 2010).
Vol. 21, issue 5 (2013) (viewed on May 21, 2013).
Keywords: United States. -- Air Force -- Safety measures -- Periodicals; United States. -- Air Force; Aircraft accidents -- United States -- Prevention -- Periodicals; Airmen -- United States -- Safety measures -- Periodicals; Airplanes, Military -- Safety measures -- Periodicals; Aeronautics, Military -- United States -- Safety measures -- Periodicals; Military History & Science; Aeronautics, Military -- Safety measures; Aircraft accidents -- Prevention; Airplanes, Military -- Safety measures; Armed Forces -- Safety measures; United States; Electronic journals